2020
DOI: 10.1038/s41467-020-18500-x
|View full text |Cite
|
Sign up to set email alerts
|

GPR101 drives growth hormone hypersecretion and gigantism in mice via constitutive activation of Gs and Gq/11

Abstract: Growth hormone (GH) is a key modulator of growth and GH over-secretion can lead to gigantism. One form is X-linked acrogigantism (X-LAG), in which infants develop GH-secreting pituitary tumors over-expressing the orphan G-protein coupled receptor, GPR101. The role of GPR101 in GH secretion remains obscure. We studied GPR101 signaling pathways and their effects in HEK293 and rat pituitary GH3 cell lines, human tumors and in transgenic mice with elevated somatotrope Gpr101 expression driven by the rat Ghrhr prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 64 publications
0
18
0
2
Order By: Relevance
“…1). A recent study in transgenic mice has demonstrated that GPR101 constitutively activates not only G s , but also G q/11 and G 12/13 , leading to GH secretion but not cell proliferation [35]. The pathogenetic mechanism may also involve the ability of GPR101 to increase GHRH secretion by the hypothalamus, accordingly to the elevated circulating GHRH levels described in some X-LAG patients [30, 36, 37].…”
Section: Pathogenesis Of Pitnets: Germline and Somatic Mutationsmentioning
confidence: 99%
“…1). A recent study in transgenic mice has demonstrated that GPR101 constitutively activates not only G s , but also G q/11 and G 12/13 , leading to GH secretion but not cell proliferation [35]. The pathogenetic mechanism may also involve the ability of GPR101 to increase GHRH secretion by the hypothalamus, accordingly to the elevated circulating GHRH levels described in some X-LAG patients [30, 36, 37].…”
Section: Pathogenesis Of Pitnets: Germline and Somatic Mutationsmentioning
confidence: 99%
“…Therefore, they further determined that the case was not X-LAG by high-definition molecular cytogenesis because the duplicated region did not contain the GPR101 gene, which proved that GPR101 was the pathogenic gene from the reverse side [33]. The latest research reported by Abboud et al [19] revealed that GPR101 could promote GH secretion without hyperplasia/tumorigenesis in HEK293 cells, GH3 cells, human somatotropinoma, and transgenic mice with elevated somatotrope Gpr101 expression, which were related to protein kinase C activation. This study showed that GPR101 expression at the mRNA level was significantly higher in X-LAG patients than in normal or acromegaly females, which was almost the same result as a previous study by Trivellin et al [14].…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, the duplication of the G-protein coupled receptor 101 (GPR101) gene is certified to be the definite pathogenesis of X-LAG by Trivellin et al [14] for the first time, and X-LAG can also occur due to somatic mosaicism in males [18]. The latest research shows that GPR101 plays an important role in GH and PRL over secretion but not hyperplasia and tumorigenesis [19]. Lacovazzo et al [20] showed that 9 patients had pituitary adenomas while 3 patients had hyperplasia in the X-LAG cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Another GPCR which has also been characterized by its striatal enrichment and its relationship to adrenergic receptors, is GPR101 [ 248 ]. It is a Gα s , Gα q/11 , and Gα 12/13 coupled receptor and is enriched in the matrix compartment of the striatum [ 248 , 249 ]. Mice lacking GPR101 display higher immobility time in the forced swim test [ 248 ].…”
Section: Orphan Gpcrs Localized In Circuitries Involved In Mddmentioning
confidence: 99%